Consumption demand - Attanasio, Orazio P. 1959- (1998)
Consumption is the largest component of GDP. Since the 1950s, the life cycle and the permanent income models have constituted the main analytical tools to the study of consumption behavior, both at the micro and at the aggregate levels. Since the late 1970s the literature has focused on versions of the model that incorporate the hypothesis of Rational Expectations and a rigorous treatment of uncertainty. In this paper, I survey the most recent contribution and assess where the life cycle model stands. My reading of the evidence and of recent developments leads me to stress two points: (i) the model can only be tested and estimated using a flexible specification of preferences and individual level data; (ii) it is possible to construct versions of the model that are not rejected by the data. One of the main problems of the approach used in the literature to estimate preferences is the lack of a consumption function.' A challenge for future research is to use preference parameter estimates to construct such functions.
Keywords: Consommation - Grande-Bretagne - Modèles économétriques; Consommation - États-Unis - Modèles économétriques; Ökonometrisches Modell; Consumption (Economics) -- Great Britain -- Econometric models; Consumption (Economics) -- United States -- Econometric models; Großbritannien; USA